William Walter Remington papers - Remington, William Walter, 1917-
Chiefly correspondence Remington gathered in furtherance of his defense against charges of perjury resulting from his denial under oath that he had participated in a Soviet espionage ring and that he had been a member of the Communist party. Correspondents include Remington's parents Frederick C. and Lillian Sutherland Remington, his wife Ann Moos Remington, and his mother-in-law Elizabeth Moos. Includes a report by an investigator to Joseph L. Rauh, Remington's defense attorney, regarding admitted Soviet spy Elizabeth Bentley, who first accused Remington of espionage.
Government official and defendant in national security cases.
Collection material in English.
Keywords: Bentley, Elizabeth; Moos, Elizabeth -- Correspondence; Remington, Ann Moos -- Correspondence; Remington, Frederick C. -- Correspondence; Remington, Lillian Sutherland -- Correspondence; Communist Party of the United States of America; Espionage, Soviet -- United States; Spies -- United States; Trials (Perjury) -- United States; Trials (Espionage) -- United States; Communists -- United States; Public officials